Strategi Pengelolaan Sampah di Pasar Tradisional Berbasis Analisis SWOT (Studi Kasus Pasar Serikat Kelarasan Bungo Setangkai Kecamatan Suliki) - Vitrah, Puja Zahara; Febriandi, Febriandi (Lembaga Yasin AlSys, 2025)
This study aims to determine 1) The waste management system at the Serikat Kelarasan Bungo Setangkai Market, Suliki District. 2) The role of traditional market traders in waste management in the Serikat Kelarasan Bungo Setangkai Market environment, Suliki District. 3) What strategies can be applied to waste management at the Serikat Kelarasan Bungo Setangkai Market based on the results of the SWOT analysis. The type of research in this study is mixed method research (combined research). Data collection techniques use observation, interviews, questionnaires, and documentation taken directly from market managers, traders, visitors, and market cleaners. The qualitative data analysis technique in this study uses the Miles and Huberman model and quantitative data uses descriptive percentages with the help of Ms. Excel. The results of the study indicate that 1) The waste management system at the Serikat Kelarasan Bungo Setangkai Market so far can be said to be not good enough in the stages of sorting, collecting, transporting, processing, and final processing of waste because it has not yet implemented waste management with an environmentally based method. 2) The role of traders in waste management in the market is also still relatively low, due to the lack of contribution and efforts of market traders in waste containers, sorting, transporting, and processing the waste they produce from the remaining sales in the market. 3) Waste management strategies that can be used in the market based on SWOT analysis include creating a waste bank, conducting socialization and counseling to the market and the community, establishing cooperation with third parties, and strengthening market institutions.